LEGAL BASIS FOR DEALING WITH THE CONSEQUENCES OF FAMILY JUDGMENTS AND ITS PROVOKING FACTORS - Akhmedova Dildora Naildjan kizi (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
: it is known that the amount of divorces in Uzbek families is less than in other nationalities. But the number of "living orphaned" children per divorced family is 2-2.5 times higher in Uzbek families. At the same time, the fact that the"culture of divorce" is at a lower level and is expressed by specific national characteristics has more consequences in Uzbek families. Accordingly, the negative complications of divorces are expressed in Uzbek families more strongly than in other nationalities. This article brings ideas and reflections on the causes, and consequences of family divorces, their impact on the psyche and upbringing of children in the family, and measures to prevent divorces.